1981
DOI: 10.1111/j.1365-2621.1981.tb04221.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Concentration on Quality of Restructured Pork Chops

Abstract: Restructured pork chops containing approximately 15% fat were manufactured from fresh hams and boston butts taken from sows. The effects of salt level (OS, OS%, l.O%, and 1.5%) and freezer storage time (0 and 30 days) on quality attributes of restructured pork chops were studied with three replications. Triangle test differences were significant for all comparisons except 1.0% and 1.5% salt groups stored for 30 days. 2-Thiobarbituric acid (TBA) values increased linearly with increasing salt levels for both 0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
2
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 7 publications
7
32
2
1
Order By: Relevance
“…In other products, the role of salt is well documented in restructured beef rolls (Pepper & Schmidt, 1975), and flaked and formed beef patties (Huffman, Cross, Campbell, & Cordray, 1981a). The results of Huffman, Ly, and Cordray (1981b) showed that addition of salt at all levels increased thiobarbituric acid (TBA) values and decreased color levels, but flavor, juiciness, and the textural properties were improved. Salt levels between 0.5 and 1.0% were recommended.…”
Section: Role Of Non-meat Ingredients Saltmentioning
confidence: 91%
“…In other products, the role of salt is well documented in restructured beef rolls (Pepper & Schmidt, 1975), and flaked and formed beef patties (Huffman, Cross, Campbell, & Cordray, 1981a). The results of Huffman, Ly, and Cordray (1981b) showed that addition of salt at all levels increased thiobarbituric acid (TBA) values and decreased color levels, but flavor, juiciness, and the textural properties were improved. Salt levels between 0.5 and 1.0% were recommended.…”
Section: Role Of Non-meat Ingredients Saltmentioning
confidence: 91%
“…Such color of meat products is commonly seen in meat product displays and is not attractive to consumers because it shows that the meat product is no longer fresh. In restructured meat products, myoglobin denaturation is affected by grinding, mixing, and multiplication of microorganisms (Govindarajan et al, 1977) and increase in temperature (Hood, 1980;Sherwin and Labuza, 2003), salt (Huffman et al, 1981;Rhee et al, 1983;Trout, 1989), and peroxide from lipid oxidation (Faustman and Cassens, 1990). The percent metmyoglobin of the semidried pork jerky samples that were prepared with various kimchi powder levels are shown in Table 2.…”
Section: A -Cmentioning
confidence: 99%
“…Huffman et al (1981) reported increase in cook yield with increase in salt level and phosphate level for restructured pork chops. Lower cook yield and correspondingly lower moisture of the cooked samples were obtained at 100°C than at 70°C (Arganosa et al 1991).…”
Section: Introductionmentioning
confidence: 96%